Obsessive Passion: A Compensatory Response to Unsatisfied Needs. Issue 2 (21st October 2015) - Lalande, Daniel; Vallerand, Robert J.; Lafrenière, Marc‐André K.; Verner‐Filion, Jérémie; Laurent, François‐Albert; Forest, Jacques; Paquet, Yvan
Abstract: The present research investigated the role of two sources of psychological need satisfaction (inside and outside a passionate activity) as determinants of harmonious (HP) and obsessive (OP) passion. Four studies were carried out with different samples of young and middle‐aged adults (e.g., athletes, musicians; total N = 648). Different research designs (cross‐sectional, mixed, longitudinal) were also used. Results showed that only a rigid engagement in a passionate activity (OP) was predicted by low levels of need satisfaction outside the passionate activity (in an important life context or in life in general), whereas both OP and a more favorable and balanced type of passion, HP were positively predicted by need satisfaction inside the passionate activity. Further, OP led to negative outcomes, and HP predicted positive outcomes. These results suggest that OP may represent a form of compensatory striving for psychological need satisfaction. It appears important to consider two distinct sources of need satisfaction, inside and outside the passionate activity, when investigating determinants of optimal and less optimal forms of activity engagement.